A photoactive copper iodide phosphine-based coordination polymer. (11th November 2020) - Benito, Quentin; Desboeufs, Nicolas; Fargues, Alexandre; Garcia, Alain; Massuyeau, Florian; Martineau-Corcos, Charlotte; Devic, Thomas; Perruchas, Sandrine
Abstract : Coordination of the polymetallic [Cu4 I4 ] center by phenyl-based-diphosphine ligands results in a coordination polymer exhibiting luminescence thermochromic properties. Abstract : A coordination polymer based on the polymetallic [Cu4 I4 ] center was synthesized by coordination with a phenyl-based-diphosphine ligand. The structure of this solid formulated as [Cu4 I4 (Ph2 P(C6 H4 )2 PPh2 )2 ] n, although crystalline, could not be completely resolved using powder X Ray diffraction analysis. Nevertheless, combining different characterization techniques, in particular 63 Cu and 31 P solid-state NMR analyses, provided insights into the polymeric structure. This coordination polymer appears to be of high dimensionality with possible interpenetrated networks, resulting in low porosity. Photoluminescence characterization revealed that the original luminescence thermochromic properties could be ascribed to the photoactive cluster unit.